Exploring the Impact of Artificial Intelligence on Research Ethics - A Systematic Review: Exploring the Impact of Artificial Intelligence on Research Ethics - A Systematic Review - Andrade-Hidalgo, Gabriel; Mio-Cango, Pedro; Iparraguirre-Villanueva, Orlando (Journal of academic ethics, 2025)
The rapid advancement of artificial intelligence (AI) has profoundly transformed many people's lives, ChatGPT being a clear example, whose capabilities have substantially influenced the automation of tasks such as writing texts and providing information sources for researchers. This review article aims to understand the impact of AI on academic writing and why its use can be considered plagiarism. The Prism method was used to analyze the studies, which initially totaled 824, and after excluding them for duplicity and by title, a total of 137 were left, of which we proceeded to review those that were open access and those that were related to the study, obtaining a total of 54 manuscripts closely related to the research topic; the results were then segmented into three questions, What are the text-matching tools that help to identify the use of AI in article writing?, What strategies are used to regulate the use of AI in writing scientific articles? and What techniques are used to detect AI-generated text?, which were key to comparing the results of the review with the findings of the authors belonging to the literature review. The results showed that, from 2022 onwards, AI became a recurring topic among researchers in China and the United States, allowing the emergence of popular techniques and software such as Turnitin or GPTZero to identify when these linguistic models were used in writing tasks, as well as strategies to regulate their use in controlled environments. In the end, it was concluded that there is a fine line between ethics and abuse of AI capabilities, and further research and study of different techniques is recommended to recognize when these tools are blatantly used.